Flexible zinc ion hybrid supercapacitor graphene-based electrode and preparation method and application thereof
By regulating the nanocomposite unit dispersion system of graphene and composite materials and the in-situ reduction assembly of metal substrates, a flexible graphene-based electrode with high mechanical properties is constructed, and the problem of poor electrochemical stability of flexible zinc ion hybrid supercapacitors in the prior art is solved, and the improvement of device performance and cost-effectiveness is achieved.
Patent Information
- Application Number
- CN202510026639.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
The existing flexible zinc ion hybrid supercapacitors have poor electrochemical stability under mechanical deformation conditions, and the binding force of the active substances and current collectors of the electrode materials is not strong, resulting in a degradation of device performance.
Through the regulation of the dispersion system of graphene and composite nanocomposite unit, combined with the in-situ reduction assembly of metal substrates, capacitive and battery-type electrodes with high mechanical properties are constructed to form a flexible graphene-based composite thin film electrode with a self-supporting structure.
It has achieved the improvement of electrochemical stability and mechanical properties of flexible zinc ion hybrid supercapacitors under different deformation conditions, and has excellent electrochemical performance and cost-effectiveness. It is suitable for portable, wearable electronic products and other fields.
Smart Images

Figure CN119694802A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of novel energy storage technology, and in particular relates to a flexible zinc ion hybrid supercapacitor graphene-based electrode and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology, portable electronic products are constantly updated and developed in the direction of flexibility, wearability and miniaturization. They are widely used in wireless communications, medical health and sensors. As an important energy supply part, flexible energy storage devices directly affect the operation and use of flexible electronic devices. Supercapacitors are energy storage devices between traditional capacitors and batteries. They have the advantages of high power density, long service life, easy flexibility and miniaturization, but their energy density is low and it is difficult to meet the needs of practical applications. Zinc ion hybrid supercapacitors, as an emerging energy storage device, are composed of battery-type and capacitor-type electrodes placed in zinc ion electrolyte. Because they can combine the high energy density of zinc ion batteries and the excellent power density and cycle stability of supercapacitors, they are considered to be a promising energy storage technology. In order to achieve efficient and safe flexible electronic systems, flexible zinc ion hybrid supercapacitors must be able to maintain good electrochemical stability under different deformation conditions. The design and construction of electrode materials and the optimization and matching of device structures are important factors affecting the performance of flexible devices.
[0003] Electrodes prepared based on traditional coating processes have weak binding forces between active materials and current collectors. Under mechanical deformation, they are easily pulverized and separated from the current collector, resulting in device performance degradation or even failure. Graphene is of great value in the construction of flexible electrodes due to its excellent mechanical properties, large specific surface area, excellent conductivity and good chemical stability. Graphene self-assembled films can be directly used as flexible electrodes without the need for adhesives or current collectors. However, when using graphene as the basic material to construct flexible electrodes, there are still problems such as serious stacking and agglomeration between graphene sheets, uneven doping distribution of composite active materials, and weak interface bonding, which makes the synergistic effect between composite materials and graphene unable to be effectively exerted. When constructing devices, there are still problems such as the inability to effectively match the capacity and cycle performance of capacitor-type and battery-type electrodes. Therefore, how to construct high-performance graphene flexible capacitor-type / battery-type electrodes and hybrid energy storage devices is of great significance to promote the widespread application of flexible zinc-ion hybrid supercapacitors in the field of flexible wearable electronic products. Summary of the invention
[0004] The purpose of the present invention is to provide a flexible zinc ion hybrid supercapacitor graphene-based electrode and its preparation method and application in view of the above-mentioned problems. Through the regulation of the graphene and composite nanocomposite unit dispersion system, the metal substrate is used for in-situ reduction assembly to construct capacitor and battery-type electrodes with high mechanical properties, and this is used as an electrode to construct a flexible zinc ion hybrid supercapacitor. The present invention has the characteristics of simple process flow, low cost, wide applicability and scalable production. The assembled energy storage device has excellent electrochemical and mechanical properties, and has broad application prospects in the fields of portable, wearable electronic products, biomedicine, health monitoring, etc.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0006] According to one aspect of the present invention, a flexible zinc ion hybrid supercapacitor graphene-based electrode is provided, wherein the electrode is composited with a flexible graphene conductive skeleton and a capacitor / pseudocapacitor or battery-type material, and the electrode is a flexible graphene-based composite thin film electrode with a self-supporting structure.
[0007] Preferably, the mass ratio of the graphene conductive skeleton to the active electrode material is 4:1-8.
[0008] Preferably, the capacitor / pseudocapacitor material is a low-dimensional carbon material, a conductive polymer, a metal oxide, a metal carbide or a metal nitride.
[0009] Preferably, the battery-type material is an inorganic metal compound, an organic electrode material or zinc metal.
[0010] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned flexible zinc ion hybrid supercapacitor graphene-based electrode, comprising the following steps:
[0011] 1) Preparation of graphene oxide monodisperse
[0012] Graphene oxide dispersions were prepared by chemical exfoliation method using graphites of different sizes as raw materials.
[0013] 2) Preparation of monodispersed solutions of capacitor / battery active materials
[0014] Using metal salts and metal oxides as raw materials, metal oxide monodispersities are prepared by hydrothermal, solvothermal and other methods; low-dimensional carbon material monodispersities are prepared by acidification and ultrasonic treatment; and polymer monodispersities are prepared by interfacial polymerization and ultrasonic dispersion.
[0015] 3) Preparation of graphene-based flexible electrodes
[0016] The graphene oxide monodisperse liquid and the capacitor / battery type active material monodisperse liquid are mixed evenly to prepare a mixed dispersion liquid, and then the zinc plate is immersed in the mixed dispersion liquid to perform reduction self-assembly, and finally dried to obtain a flexible graphene-based composite electrode.
[0017] Preferably, the concentration of the graphene oxide dispersion is 5-15 mg / mL.
[0018] Preferably, the concentration of the capacitor / battery type active material monodisperse liquid is 1-15 mg / mL.
[0019] Preferably, in step 3), the mixing volume ratio of the graphene dispersion and the active material dispersion is 2:1-8.
[0020] Preferably, the metal substrate in step 3) is any one of nickel (Ni), copper (Cu), zinc (Zn), aluminum (Al) and titanium (Ti) metal foil.
[0021] Preferably, in step 3), the metal substrate is immersed in the mixed dispersion for reduction self-assembly for 0.5-6 hours.
[0022] Preferably, the drying treatment in step 3) is one of natural drying induced by water evaporation, constant temperature drying and freeze drying.
[0023] According to another aspect of the present invention, a flexible zinc ion hybrid supercapacitor is provided, which is prepared using the flexible graphene-based electrode.
[0024] Preferably, the flexible zinc ion hybrid supercapacitor is integrated with one of an LED lamp, a sensor and a wearable electronic product as an energy storage device to drive the operation of such electronic products.
[0025] The beneficial effects of the present invention are:
[0026] 1. The graphene used in the present invention has good mechanical properties and high electrical conductivity, and can be directly used as a flexible electrode or self-supporting substrate without the need for an adhesive or current collector. The capacity of the flexible graphene-based capacitive electrode can be further improved by in-situ self-assembly of a graphene double layer and a pseudocapacitive material composite unit. Graphene is used in the construction of flexible battery electrodes, which can serve as a flexible self-supporting skeleton and provide a good conductive channel, which is conducive to achieving high rate performance and cycle stability of battery electrodes.
[0027] 2. The present invention maximizes the synergistic effect of graphene and capacitor / battery active materials by regulating the interface structure and micromorphology between the two at the micro and macro scales, which is conducive to achieving a balance and matching between flexible graphene-based capacitor electrodes and battery electrodes in terms of capacity, rate and cycle stability, and ultimately obtaining a high-performance flexible zinc ion hybrid supercapacitor.
[0028] 3. The preparation process of the present invention has the advantages of low cost, wide applicability and scalable production. The assembled graphene-based flexible zinc ion hybrid supercapacitor has excellent electrochemical and mechanical properties, and has broad application prospects in portable electronic products, biomedicine, health monitoring and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an optical photograph of the V2O5@RGO-dried composite film obtained in Example 1 of the present invention.
[0030] Figure 2 a and Figure 2 b is a cross-sectional scanning electron microscope image of the V2O5@RGO-dried composite film obtained in Example 1 of the present invention.
[0031] Figure 3 a and Figure 3 b is a cross-sectional scanning electron microscope image of the V2O5@RGO-cold-dried composite membrane obtained in Comparative Example 1 of the present invention.
[0032] Figure 4 1 and 2. The stress-strain curves of the V2O5@RGO-dried composite film obtained in Example 1 of the present invention and the V2O5@RGO-cold-dried composite film obtained in Comparative Example 1.
[0033] Figure 5 This is a comparison chart of the surface resistance of the V2O5@RGO-dried composite film obtained in Example 1 of the present invention and the V2O5@RGO-cold-dried composite film obtained in Comparative Example 1.
[0034] Figure 6 3. The charge and discharge curves of the C||V2O5@RGO device prepared in Example 1 of the present invention and Comparative Example 1.
[0035] Figure 7 The flexible soft package C||V2O5@RGO-drying device of Example 1 of the present invention is flat ( Figure 7 a) and curl( Figure 7 b) Optical photo of the LED screen lit up in state.
[0036] Figure 8 a and Figure 8 b is a cross-sectional scanning electron microscope image of the CNTs@RGO-naturally dried composite film obtained in Example 2 of the present invention.
[0037] Fig. 9 a and Fig. 9 b is a cross-sectional scanning electron microscope image of the CNTs@RGO-freeze-dried composite film obtained in Comparative Example 2 of the present invention.
[0038] Fig.10 These are the stress-strain curves of the CNTs@RGO-naturally dried composite film obtained in Example 2 of the present invention and the CNTs@RGO-freeze dried composite film obtained in Comparative Example 2.
[0039] Fig.11 These are the IV curves of the CNTs@RGO-naturally dried composite membrane obtained in Example 2 of the present invention and the CNTs@RGO-freeze dried composite membrane obtained in Comparative Example 2.
[0040] Fig.12 These are the charge and discharge curves of the Zn||CNTs@RGO-natural drying device prepared in Example 2 of the present invention under different bending conditions. DETAILED DESCRIPTION
[0041] In order to better understand the content of the present invention, the content of the present invention is described in detail below in conjunction with specific embodiments.
[0042] Example 1
[0043] Using graphene and V2O5 as composite units and metal Zn plate as substrate, in-situ self-assembly is performed to prepare flexible battery-type electrodes, and Zn(CF3SO3)2 aqueous solution is used as electrolyte and carbon is used as negative electrode to assemble zinc ion hybrid supercapacitor, including the following steps:
[0044] 1) Preparation of graphene oxide (GO) monodisperse
[0045] The GO dispersion used was prepared by a modified Hummer method, and the specific preparation process is as follows:
[0046] First, 3g of graphite powder was placed in a 500mL beaker, 70mL of 98% H2SO4 was added, and stirred at room temperature for 30min; the beaker was moved to an ice-water bath, 1.5g of NaNO3 was added under stirring, and stirring was continued for 30min; 9g of KMnO4 was slowly added, and after stirring in the ice-water bath for 30min, the beaker was moved to a 38℃ warm water bath and stirred continuously for 45min; the beaker was moved to an ice-water bath again, and 140mL of ultrapure water was slowly added under stirring; the ice-water bath was removed, and 200mL of ultrapure water was quickly added; 20mL of 30% H2O2 was slowly added under stirring, and stirring was continued for 5min; the obtained mixture was centrifuged and washed with 37% HCl solution, and then centrifuged and washed with ultrapure water until it was nearly neutral. Finally, an appropriate amount of ultrapure water was added to the dispersion to dilute it to 500mL, and the bottom precipitate was removed by centrifugation after ultrasonication for 5h to obtain a GO dispersion.
[0047] 2) Preparation of V2O5 monodisperse
[0048] First, 0.728 g of commercial V2O5, 10 mL of H2O2 (30%) and 60 mL of ultrapure water were mixed and stirred for 1 h to obtain a reddish-brown transparent solution; the above solution was transferred to a stainless steel high-pressure reactor with a 100 mL polytetrafluoroethylene liner; the reactor was placed in a 190° C. forced air oven and reacted for 3 h; after the reaction was completed, the reaction was cooled to room temperature to obtain a well-dispersed V2O5 colloid.
[0049] 3) Preparation of graphene / V2O5 composite film
[0050] GO and V2O5 were prepared to a concentration of 10 mg mL -1 dispersion; the GO dispersion and the V2O5 dispersion were mixed in a volume ratio of 1:1, and ultrasonically treated for 30 minutes to obtain a mixed dispersion of the two; the zinc foil was immersed in 10 mL of the mixed dispersion to react for 2 hours to obtain a RGO@V2O5 film; after removing the zinc foil and unreacted materials, the film was repeatedly immersed and washed with 0.001 M HCl solution and deionized water, respectively; finally, the RGO@V2O5 film was dried at a constant temperature of 40°C, and the obtained film was marked as V2O5@RGO-dried.
[0051] 4) Preparation of C||V2O5@RGO-dried devices
[0052] The prepared V2O5@RGO-dried film was used as the positive electrode, the carbon electrode as the negative electrode, the 2MZn(CF3SO3)2 aqueous solution as the electrolyte, and the filter paper as the diaphragm to assemble the CR2032 button battery by the traditional method. The flexible soft-pack device is made by sandwiching the diaphragm moistened with electrolyte between the V2O5@RGO-dried film positive electrode and the carbon negative electrode to form a sandwich structure, and finally encapsulating it with aluminum-plastic film.
[0053] Comparative Example 1
[0054] Changing the drying method of RGO@V2O5 film includes the following steps:
[0055] 1) Preparation of GO monodispersity
[0056] The GO dispersion used was prepared by a modified Hummer method, and the specific preparation process is as follows:
[0057] First, 3g of graphite powder was placed in a 500mL beaker, 70mL of 98% H2SO4 was added, and stirred at room temperature for 30min; the beaker was moved to an ice-water bath, 1.5g of NaNO3 was added under stirring, and stirring was continued for 30min; 9g of KMnO4 was slowly added, and after stirring in the ice-water bath for 30min, the beaker was moved to a 38℃ warm water bath and stirred continuously for 45min; the beaker was moved to an ice-water bath again, and 140mL of ultrapure water was slowly added under stirring; the ice-water bath was removed, and 200mL of ultrapure water was quickly added; 20mL of 30% H2O2 was slowly added under stirring, and stirring was continued for 5min; the obtained mixture was centrifuged and washed with 37% HCl solution, and then centrifuged and washed with ultrapure water until it was nearly neutral. Finally, an appropriate amount of ultrapure water was added to the dispersion to dilute it to 500mL, and the bottom precipitate was removed by centrifugation after ultrasonication for 5h to obtain a GO dispersion.
[0058] 2) Preparation of V2O5 monodisperse
[0059] First, 0.728 g of commercial V2O5, 10 mL of H2O2 (30%) and 60 mL of ultrapure water were mixed and stirred for 1 h to obtain a reddish-brown transparent solution; the above solution was transferred to a stainless steel high-pressure reactor with a 100 mL polytetrafluoroethylene liner; the reactor was placed in a 190° C. forced air oven and reacted for 3 h; after the reaction was completed, the reaction was cooled to room temperature to obtain a well-dispersed V2O5 colloid.
[0060] 3) Preparation of graphene / V2O5 composite film
[0061] GO and V2O5 were prepared to a concentration of 10 mg mL -1 dispersion; the GO dispersion and the V2O5 dispersion were mixed in a volume ratio of 1:1, and ultrasonically treated for 30 minutes to obtain a mixed dispersion of the two; the zinc foil was immersed in 10 mL of the mixed dispersion to react for 2 hours to obtain a V2O5@RGO film; after removing the zinc foil and the unreacted materials, the film was repeatedly soaked and washed with 0.001 M HCl solution and deionized water, respectively; finally, the V2O5@RGO film was dried by freeze-drying, and the obtained film was marked as V2O5@RGO-cold-dried.
[0062] 4) Preparation of C||V2O5@RGO-cold-dried devices
[0063] The prepared V2O5@RGO-cold-dried film was used as the positive electrode, the carbon electrode as the negative electrode, the 2MZn(CF3SO3)2 aqueous solution as the electrolyte, and the filter paper as the diaphragm to assemble the CR2032 button cell by the traditional method. The flexible soft-pack device was assembled into a sandwich structure by sandwiching the diaphragm moistened with electrolyte between the V2O5@RGO-cold-dried film positive electrode and the carbon negative electrode, and finally encapsulated with aluminum-plastic film.
[0064] The optical photograph of the V2O5@RGO-dried composite film obtained in Example 1 is as follows Figure 1 As shown. From the cross-sectional scanning electron microscope image ( Figure 2 ) It can be seen that the film presents a structure of RGO nanosheets and V2O5 nanosheets stacked layer by layer. Compared with the V2O5@RGO-dried prepared by natural drying in Example 1, the V2O5@RGO-cold dried prepared by freeze drying in Comparative Example 1 ( Figure 3 ), there is a large distance between the layers and they are not tightly connected to each other, which is not conducive to the improvement of electronic transmission and mechanical properties.
[0065] The stress-strain curves of the V2O5@RGO-dried composite film obtained in Example 1 and the V2O5@RGO-cold-dried composite film obtained in Comparative Example 1 were tested by a mechanical tester (DMA). Figure 4 As shown in the figure, the V2O5@RGO-dried composite film can withstand a tensile stress of 63.3MPa, and its Young's modulus is as high as 7.6GPa, which is much higher than that of the V2O5@RGO-cold-dried composite film, indicating that the composite film has excellent mechanical properties. By testing the IV curve of the film, the surface resistance of the V2O5@RGO-dried composite film was calculated to be 30.2Ωsq -1 ( Figure 5 ), which is smaller than that of V2O5@RGO-cold-dried composite film, indicating that the composite structure obtained by constant temperature drying at 40 °C has higher conductivity.
[0066] The electrochemical performance of the zinc ion hybrid supercapacitors obtained in Example 1 and Comparative Example 1 was tested. Figure 6 It is the constant current charge and discharge curve of the device at a current density of 0.1A / g. Figure 6 The test results show that at a current density of 0.1 A / g, the specific capacity of the C||V2O5@RGO-dried device is 73.31 mAh / g, which is higher than the specific capacity of the C||V2O5@RGO-cold-dried device.
[0067] The flexible soft-package C||V2O5@RGO-dried device is connected to the LED screen as an energy storage device to explore the practical application performance of the flexible device. Figure 7As shown, two soft-package devices connected in series can light up the LED screen with the word "NKU". Even when curled significantly, the soft-package device can still supply energy to the LED screen normally, further demonstrating the application potential of V2O5@RGO-dried film in flexible batteries.
[0068] Example 2
[0069] Graphene and multi-walled carbon nanotubes (MWCNTs) are used as composite units, and a metal Zn plate is used as a substrate to perform in-situ self-assembly to prepare a flexible capacitive electrode, and a ZnSO4 aqueous solution is used as an electrolyte and Zn is used as a negative electrode to assemble a zinc ion hybrid supercapacitor, including the following steps:
[0070] 1) Preparation of GO monodispersity
[0071] The GO dispersion used was prepared by a modified Hummer method, and the specific preparation process is as follows:
[0072] First, place 3g of graphite powder in a 500mL beaker, add 70mL of 98% H2SO4, and stir at room temperature for 30min; move the beaker to an ice water bath, add 1.5g of NaNO3 while stirring, and continue stirring for 30min; slowly add 9g of KMnO4, stir in the ice water bath for 30min, then move the beaker to a 38℃ warm water bath and continue stirring for 45min; move the beaker to an ice water bath again, slowly add 140mL of ultrapure water while stirring; remove the ice water bath, quickly add 200mL of ultrapure water; slowly add 20mL of 30% H2O2 while stirring, and continue stirring for 5min; centrifuge the resulting mixture with 37% HCl solution, and then centrifuge with ultrapure water until it is nearly neutral. Finally, add an appropriate amount of ultrapure water to the dispersion to dilute it to 500mL, and after ultrasonication for 5h, centrifuge to remove the bottom precipitate to obtain a GO dispersion; finally, prepare it to a concentration of 10mg mL -1 GO dispersion.
[0073] 2) Preparation of MWCNTs monodispersity
[0074] 1g of commercial MWCNTs, 40mL of concentrated HNO3 (68%) and 120mL of concentrated H2SO4 (98%) were stirred and mixed, and condensed and refluxed at 80°C for 1h; after cooling naturally to room temperature, the acidified MWCNTs were filtered out by vacuum filtration and repeatedly washed with deionized water until neutral; the acidified MWCNTs were dried by freeze drying; finally, the concentration was 2mgmL -1 of dispersion.
[0075] 3) Preparation of graphene / MWCNTs composite films
[0076] GO dispersion and MWCNTs dispersion were mixed in a ratio of 1:1 and ultrasonically treated for 30 minutes to obtain a mixed dispersion of the two; zinc foil was immersed in 10 mL of the mixed dispersion and reacted for 2 hours to obtain a CNTs@RGO hydrogel film; after removing the zinc foil and unreacted materials, the film was repeatedly soaked and washed with 0.001 M HCl solution and deionized water, respectively; finally, the CNTs@RGO film was naturally dried at room temperature, and the obtained film was marked as CNTs@RGO-natural drying.
[0077] 4) Preparation of Zn||CNTs@RGO devices
[0078] The prepared CNTs@RGO-natural drying film was used as the positive electrode, the Zn electrode was used as the negative electrode, the 2M ZnSO4 aqueous solution was used as the electrolyte, and the filter paper was used as the separator to assemble the CR2032 button battery by the traditional method. The flexible soft package device was prepared by sandwiching the separator moistened with the electrolyte between the CNTs@RGO-natural drying film positive electrode and the Zn negative electrode to form a sandwich structure, and finally encapsulating it with an aluminum-plastic film.
[0079] Comparative Example 2
[0080] Changing the drying method of CNTs@RGO film includes the following steps:
[0081] 1) Preparation of GO monodispersity
[0082] The GO dispersion used was prepared by a modified Hummer method, and the specific preparation process is as follows:
[0083] First, place 3g of graphite powder in a 500mL beaker, add 70mL of 98% H2SO4, and stir at room temperature for 30min; move the beaker to an ice water bath, add 1.5g of NaNO3 while stirring, and continue stirring for 30min; slowly add 9g of KMnO4, stir in the ice water bath for 30min, then move the beaker to a 38℃ warm water bath and continue stirring for 45min; move the beaker to an ice water bath again, slowly add 140mL of ultrapure water while stirring; remove the ice water bath and quickly add 200mL of ultrapure water; slowly add 20mL of 30% H2O2 while stirring, and continue stirring for 5min; centrifuge the resulting mixture with 37% HCl solution, and then centrifuge with ultrapure water until it is nearly neutral. Finally, add an appropriate amount of ultrapure water to the dispersion to dilute it to 500mL, and after ultrasonication for 5h, centrifuge to remove the bottom precipitate to obtain a GO dispersion. Finally, prepare it to a concentration of 10mg mL -1 GO dispersion.
[0084] 2) Preparation of MWCNTs monodispersity
[0085] 1g of commercial MWCNTs, 40mL of concentrated HNO3 (68%) and 120mL of concentrated H2SO4 (98%) were stirred and mixed, and condensed and refluxed at 80°C for 1h; after cooling naturally to room temperature, the acidified MWCNTs were filtered out by vacuum filtration and repeatedly washed with deionized water until neutral; the acidified MWCNTs were dried by freeze drying; finally, the concentration was 2mgmL -1 of dispersion.
[0086] 3) Preparation of graphene / MWCNTs composite films
[0087] GO dispersion and MWCNTs dispersion were mixed in a ratio of 1:1 and ultrasonically treated for 30 minutes to obtain a mixed dispersion of the two; zinc foil was immersed in 10 mL of the mixed dispersion to react for 2 hours to obtain a CNTs@RGO hydrogel film; after removing the zinc foil and unreacted materials, the film was repeatedly soaked and washed with 0.001 M HCl solution and deionized water, respectively; finally, the CNTs@RGO film was dried by freeze-drying, and the obtained film was marked as CNTs@RGO-freeze-dried.
[0088] 4) Preparation of Zn||CNTs@RGO devices
[0089] The prepared CNTs@RGO-freeze-dried film was used as the positive electrode, the Zn electrode was used as the negative electrode, the 2M ZnSO4 aqueous solution was used as the electrolyte, and the filter paper was used as the separator to assemble the CR2032 button battery by the traditional method. The flexible soft-pack device was made by sandwiching the separator moistened with the electrolyte between the CNTs@RGO-freeze-dried film positive electrode and the Zn negative electrode to form a sandwich structure, and finally encapsulating it with an aluminum-plastic film.
[0090] The cross-sectional scanning electron microscopy image of the CNTs@RGO-natural drying composite membrane obtained in Example 2 is as follows: Figure 8 As shown, the film presents a dense layer-by-layer stacking structure. Compared with the CNTs@RGO-natural drying film prepared by natural drying method in Example 2, the CNTs@RGO-freeze drying film prepared by freeze drying method in Comparative Example 2 ( Fig. 9 ), there is a large distance between the layers and they are not tightly connected to each other, which is not conducive to the improvement of electronic transmission and mechanical properties.
[0091] The stress-strain curves of the CNTs@RGO-natural drying composite film obtained in Example 2 and the CNTs@RGO-freeze drying composite film obtained in Comparative Example 2 were tested by a mechanical tester (DMA). Fig.10As shown in the figure, the CNTs@RGO-natural drying composite film can withstand a tensile stress of 92.45MPa, and its Young's modulus is as high as 2.48GPa, which is much higher than that of the CNTs@RGO-freeze drying composite film, indicating that the composite film has excellent mechanical properties. Fig.11 ), the surface resistance of CNTs@RGO-natural drying composite film was calculated to be 7.05Ωsp -1 , which is smaller than that of CNTs@RGO-freeze-dried composite film, indicating that the composite structure obtained by natural drying method has higher conductivity.
[0092] The electrochemical performance of the flexible zinc ion hybrid supercapacitor obtained in Example 2 was tested. Fig.12 is the constant current charge and discharge curve of the device under different bending states. Fig.12 The test results show that at a current density of 0.1 A / g, the specific capacity of the Zn||CNTs@RGO-naturally dried thin film device is 42.6 mAh / g. Even when bent 180°, the specific capacity remains almost unchanged, demonstrating the excellent electrochemical stability of the Zn||CNTs@RGO soft-package device under different bending states.
[0093] The above embodiments are only used to illustrate the present invention, and should not be understood as limiting the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made to the present invention within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A flexible zinc ion hybrid supercapacitor graphene-based electrode, characterized in that: The electrode is composited with a flexible graphene conductive skeleton and a capacitor / pseudocapacitor or battery-type material. The electrode is a flexible graphene-based composite film electrode with a self-supporting structure. The mass ratio of the graphene conductive skeleton to the active electrode material is 4:1-8.
2. The flexible zinc ion hybrid supercapacitor graphene-based electrode according to claim 1, characterized in that: The capacitor / pseudocapacitor material is a low-dimensional carbon material, a conductive polymer, a metal oxide, a metal carbide or a metal nitride.
3. The flexible zinc ion hybrid supercapacitor graphene-based electrode according to claim 1, characterized in that: The battery type material is an inorganic metal compound, an organic electrode material or zinc metal.
4. A method for preparing a graphene-based electrode for a flexible zinc ion hybrid supercapacitor according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Preparation of graphene oxide monodisperse Graphites of different sizes are used as raw materials and a graphene oxide dispersion is prepared by a chemical exfoliation method. The concentration of the graphene oxide dispersion is 5-15 mg / mL. 2) Preparation of monodispersed solutions of capacitor / battery active materials Using metal salts and metal oxides as raw materials, metal oxide monodispersities are prepared by hydrothermal, solvent thermal and other methods; low-dimensional carbon material monodispersities are prepared by acidification and ultrasonic treatment; polymer monodispersities are prepared by interfacial polymerization and ultrasonic dispersion; the concentration of the active material monodispersity is 1-15 mg / mL. 3) Preparation of graphene-based flexible electrodes The graphene oxide monodisperse liquid and the capacitor / battery type active material monodisperse liquid are uniformly mixed to prepare a mixed dispersion liquid, and then the metal substrate is immersed in the mixed dispersion liquid for reduction self-assembly, and finally dried to obtain a flexible graphene-based composite electrode.
5. The method for preparing a graphene-based electrode for a flexible zinc ion hybrid supercapacitor according to claim 4, characterized in that: In the step 3), the mixing volume ratio of the graphene dispersion and the active material dispersion is 2:1-8.
6. The method for preparing a graphene-based electrode for a flexible zinc ion hybrid supercapacitor according to claim 4, characterized in that: In the step 3), the metal substrate is any one of nickel (Ni), copper (Cu), zinc (Zn), aluminum (Al) and titanium (Ti) metal foil.
7. The method for preparing a graphene-based electrode for a flexible zinc ion hybrid supercapacitor according to claim 4, characterized in that: In the step 3), the metal substrate is immersed in the mixed dispersion for reduction self-assembly for 0.5-6 hours.
8. The method for preparing a graphene-based electrode for a flexible zinc ion hybrid supercapacitor according to claim 4, characterized in that: The drying process in step 3) is one of natural drying induced by water evaporation, constant temperature drying and freeze drying.
9. A flexible zinc ion hybrid supercapacitor, characterized in that: Prepared using the flexible graphene-based electrode described in claim 1.
10. The use of a flexible zinc ion hybrid supercapacitor according to claim 9, characterized in that: Flexible zinc-ion hybrid supercapacitors are integrated as energy storage devices with LED lights, sensors, and wearable electronic products to drive the operation of such electronic products.